Dynamics of Mother Tongue Shifting in Contemporary Cultural Change - Haeri, Zul; Suryanirmala, Neni (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Indonesian as a national language and mother tongue (regional) as a language of cultural preservation, Indonesian language and mother tongue (regional) cannot work together, due to several factors such as migration, social class and education which make Indonesian a language shift dynamic. mother (region) in cultural change. The theory used is sociolinguistics. Obtaining data uses the listen and note method. Data analysis uses a population census conducted by Samuel and Handono. The results of the research that has been carried out show that Indonesian is used daily by 59.5 percent of the total population of Indonesia and 45.43 of the state administration in the Central Java region, based on existing phenomena. Indonesia will become an Indonesian population, which means that all of them will become Indonesian speakers because of the rapid growth in population which cannot be separated from the government through language planning as outlined in national language politics which is promoted through press, economic and social teaching.